(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Tennessee Williams(March 26, 1911 – February 25, 1983) born Thomas Lanier Williams, was anAmerican playwright who received many of the top theatrical awards for hisworks of drama. He moved to New Orleans in 1939 and changed his name to"Tennessee", the Southeastern U.S. state, his father’s birthplace.